2015
DOI: 10.1073/pnas.1416285112
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical coproporphyrin-dependent bacterial heme biosynthesis pathway that does not use protoporphyrin

Abstract: It has been generally accepted that biosynthesis of protoheme (heme) uses a common set of core metabolic intermediates that includes protoporphyrin. Herein, we show that the Actinobacteria and Firmicutes (high-GC and low-GC Gram-positive bacteria) are unable to synthesize protoporphyrin. Instead, they oxidize coproporphyrinogen to coproporphyrin, insert ferrous iron to make Fe-coproporphyrin (coproheme), and then decarboxylate coproheme to generate protoheme. This pathway is specified by three genes named hemY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
252
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(268 citation statements)
references
References 46 publications
10
252
2
1
Order By: Relevance
“…Recently, Dailey and co-workers proposed a novel haeme biosynthesis pathway for Gram-positive bacteria in which HemQ acts as a coprohaeme decarboxylase to yield protohaeme; in this reaction, coprohaeme has to bind to HemQ, react with presumably H 2 O 2 to release two CO 2 molecules to yield and release haeme b. This finding is also supported by other studies [7][8][9][10]. Nevertheless, the mechanism of this reaction is unknown.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Recently, Dailey and co-workers proposed a novel haeme biosynthesis pathway for Gram-positive bacteria in which HemQ acts as a coprohaeme decarboxylase to yield protohaeme; in this reaction, coprohaeme has to bind to HemQ, react with presumably H 2 O 2 to release two CO 2 molecules to yield and release haeme b. This finding is also supported by other studies [7][8][9][10]. Nevertheless, the mechanism of this reaction is unknown.…”
Section: Introductionmentioning
confidence: 64%
“…For LmHemQ, it was shown that the protein is able to bind and release haeme reversibly, indicating a regulatory haeme sensing role during haeme biosynthesis in Gram-positive bacteria [5], as was also suggested by physiological studies of SaHemQ and BsHemQ [3,4]. Reversible haeme binding of the cofactor (substrate) is also a prerequisite for HemQs to act as coprohaeme decarboxylase (thereby binding coprohaeme and releasing protohaeme) [7].…”
Section: Introductionmentioning
confidence: 71%
“…To determine whether '882 retains activity against CgoX from other Gram-positive organisms, recombinant Bacillus subtilis and P. acnes CgoX were purified (7). K m and V max values were determined to characterize baseline activity of the enzymes, and each was tested for '882-induced activation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Until recently, it was thought that the heme biosynthesis pathway was conserved across all species, limiting its utility as a potential therapeutic target to treat infectious diseases. However, Dailey et al (7,8) discovered that Gram-positive bacteria use a distinct pathway to synthesize the critical cellular cofactor heme (Fig. 1A).…”
mentioning
confidence: 99%
See 1 more Smart Citation